A COMPARATIVE ANALYSIS OF THE DEGREE OF FINANCIAL LEVERAGE BETWEEN PT UNILEVER INDONESIA AND PT WINGS GROUP - Wiwik Fitria Ningsih; Hamzah Fansuri Yusuf; Setyawardahna Nugraha (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2026)
This study aims to analyze the comparison of the Degree of Financial Leverage (DFL) between PT Unilever Indonesia Tbk and PT Wings Group. DFL is important to measure because it reflects the extent of change in earnings per share resulting from changes in earnings before interest and taxes, thus serving as a key indicator of a company's financial risk. These two companies are compared because both are major players in the consumer goods industry in Indonesia with significant market shares, yet they have different ownership structures and operational strategies, making it interesting to examine their risk differences. This research is a quantitative comparative study using the financial statement data of both companies for the period 2020-2024. Sampling was conducted using a purposive sampling method, with the research samples being PT Unilever Indonesia Tbk and PT Wings Group. Data were collected through financial statement documentation techniques and analyzed using an Independent Sample t-Test. The descriptive results show that PT Wings Group has a higher and more fluctuating average DFL compared to PT Unilever Indonesia, whose DFL is more stable. However, the results of the Independent Sample t-Test indicate that there is no statistically significant difference in DFL between the two companies. The financial risk inherent in the capital structure of both companies is statistically within a balanced range within the same industry.